Problems of Commissioning of Technical Expert Examination of Documents (Law and Safety, 2021)
Certain problems that arise during the commissioning of technical expert examination of documents have been studied and analyzed. It has been clarified that they are related to the definition of the type of expert examination, the formulation of the questions to an expert regarding the objects of the examination and the preparation of materials to be examined. It has been noted that the use of special experience is needed for qualitative investigation of criminal offenses. Such experience is used in criminal proceedings in various forms. One of such forms is the commissioning of forensic examinations. One of the most common types of such examinations is technical examination of documents. It solves both diagnostic and identification issues aimed at establishing the fact of a crime, the modus operandi of a crime and the person who committed a crime. Its results are evidence in criminal proceedings.The ways of solving the problems of commissioning of technical examination of documents have been determined. It has been proved that it is necessary to properly organize the interaction between the initiator of the examination (legal entity or individual) and the expert in order to solve the considered problems. If necessary, one should address the expert institution where the examination is planned to be conducted, and get advice on the possibilities of technical examination of documents depending on the circumstances of the case and the objects of the research. It is advisable to provide expert institutions with modern technical means that should allow us to conduct high-quality and full examination.It has been offered to improve the methodological materials for the commissioning and conduction of technical examination of documents in accordance with modern scientific and technical capabilities.
Keywords: examination of documents; criminalistics expert examination; experience in criminal proceedings; criminal investigation technique; technical expert examination of documents